2019
DOI: 10.1049/iet-rpg.2018.6054
|View full text |Cite
|
Sign up to set email alerts
|

Structural responses suppression for a barge‐type floating wind turbine with a platform‐based TMD

Abstract: As the ocean environment is more complex than the land environment, the offshore wind turbines especially the floating types generally suffer significant structural loads. In this study, in order to carry out the accurate simulation and analysis for the dynamic characteristics of a barge‐type floating wind turbine, a detailed turbine model including the complete drivetrain is constructed. Additionally, the structural responses of the wind turbine are mitigated by using a single‐degree of freedom tuned mass dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In [19], it is shown how the structural responses of the floating wind turbine are mitigated by using a single-degree of freedom tuned mass damper that was installed in the platform. Based on a new model that combines multi-body model and external control codes, the turbine model coupled with the TMD is simulated under wind and wave loads.…”
Section: Related Workmentioning
confidence: 99%
“…In [19], it is shown how the structural responses of the floating wind turbine are mitigated by using a single-degree of freedom tuned mass damper that was installed in the platform. Based on a new model that combines multi-body model and external control codes, the turbine model coupled with the TMD is simulated under wind and wave loads.…”
Section: Related Workmentioning
confidence: 99%
“…According to this last consideration and taking the cue from the implications set by the Lyapunov direct method, it can be said that the controlled block dynamics are asymptotically stable with timedomain performances determined by the value of the control parameters (i.e., q 12 , q 22 ). [48][49][50][51] Although in Equation (13) three coefficients q 12 , q 22 , and r appear, the optimal control law depends only on the two independent coefficients that are the ratiosq 12 = q 12 =r andq 22 = q 22 =r . Several analyses are performed varying these two independent coefficients.…”
Section: Control Lawmentioning
confidence: 99%
“…One of the most representative of these is an active mass damper (AMD); the essence of passive dampers is mass-spring-damper systems, which can reduce vibration by changing the resonance characteristics of structures, among which a tuned mass damper (TMD) is the most widely used. Researchers have found that the reasonable configuration of an AMD [13][14][15] and a TMD [16][17][18] can reduce the vortex-induced response of the structure and reduce the occurrence of instability. However, the design of auxiliary dampers must match the mass and stiffness of structures themselves, otherwise it will aggravate the vibration of structures, the auxiliary dampers will not weaken the existing vortex-induced load, and the fatigue damage problem of structures will not be effectively solved.…”
Section: Introductionmentioning
confidence: 99%